The THE EFFECT OF FLY SWATTER GAME ON STUDENTS’ VOCABULARY AT THE SEVENTH GRADE STDENTS OF MTsS ULUMUDDIN UTEUNKOT CUNDA LHOKSEUMAWE - Erlidawati; Misrina (Jurnal Cinta Nusantara, 2024)
The purpose of this research was to prove whether the application of fly swatter game gave a significant effect to students’ vocabulary. In this research, the researcher used quantitative data approach by using quasi experimental design, the population consisted of five classes (125 students) of seventh grade in MTsS Ulumuddin academic year 2020/2021. In which the two classes as sample, class VII-6 as experimental group and class VII-7 as control group. The researcher used simple random sampling in determining the sample. The instrument used to collect data was the pre-test and post-test. As the result, the researcher found that the students’ achievement in experimental group was higher than control group. This was proved by the result of t-test (2,54) was higher than t-table in significance 0,05 (2,0126). In this study, It is suggested to the teachers should use fly swatter game as an innovative teaching in improving students’ vocabulary.